Prevalencia de Mycobacterium spp. en canales de bovinos sacrificados en centro de faenamiento del cantón El Carmen - Álvarez Reyes, Karla Nallelhy (2023)
The purpose of this study was to evaluate the prevalence of Mycobacterium spp., in carcasses of bovines slaughtered in the slaughterhouse in El Carmen canton-Manabí , where a population of 324 bovines was left to identify lesions compatible with Bovine Tuberculosis (TB) during 6 weeks, for this, the ante-mortem recording technique was used, in which the information was compiled according to age, and sample selection for the convenience of the animals and the observation technique to identify the color and texture of the lymph nodes. Post mortem, 51 samples were taken from the affected lymph nodes or with lesions compatible with tuberculosis in the prescapular and inguinal areas, taking into consideration the diameter, color and texture; in the laboratory phase, the identification of Mycobacterium spp. was carried out by sowing in culture media (Stonebrink ST, Ogawa Kudoh OK and Ziehl-Neelsen staining) in the samples taken, it was raised in the Laboratorio Nacional de Salud Pública-INSPI-Dr. Leopoldo Izquieta Pérez located in Guayaquil city, where 27 samples with growth of Mycobacterium spp. which means the 8.33% prevalence of Mycobacterium bovis of the total population studied, considered as high prevalence. The 27 samples correspond to 19 animals where eight appeared in both media, ten in ST and 1 in OK. In addition, the Ziehl–Neelsen staining resulted in 1 positive for BAAR (Bacilo Ácido Alcohol Resistente).